EFEKTIVITAS PEMANFAATAN HASIL ALAT UNGKAP MASALAH (AUM) OLEH GURU BK DI SMP NEGERI DAN SWASTA DI KECAMATAN PADANG UTARA KOTA PADANG - Putri, Kurnia Dewi (Bimbingan dan Konseling, 2014)
This research is motivated there are some guidance and counseling teachers who do not utilize yet the results of AUM effectively. This study aimed to describe the effectiveness of utilization of Public AUMâs results by guidance and counseling teachers of national junior school and privates junior school northern Padang district, 2) the effectiveness of the utilization of AUM PTSDL by guidance and counseling teacher of national junior school and privates junior school northern Padang district. This type of research is a qualitative, This study took six teachers guidance and counseling in Junior High School and a private in the District of North Padang. As research informants they were: SMP BUNDA, KORPRI, 25 and MTsN Padang. Data were collected through interviews and documentation of the effectiveness of utilization of Public AUMâs and AUM PTSDL by guidance and counseling teachers. From the analysis of interviews revealed that guidance and counseling teachers have already used the results of AUM in activities such as guidance and counseling services, but it is still found that some schools have not utilized it optimally. Based on the results of the study guidance and counseling teachers are recommended to effectively utilize the results AUM, from processing, giving service and follow-up of the servicesâ results that have been provided.